Maternal Characteristics, Pregnancy Complications, and Adverse Birth Outcomes Among Women With Disabilities. Issue 12 (December 2015) - Mitra, Monika; Clements, Karen M.; Zhang, Jianying; Iezzoni, Lisa I.; Smeltzer, Suzanne C.; Long-Bellil, Linda M.
Abstract : Objectives: The objective of this study is to describe the maternal characteristics, pregnancy complications, and birth outcomes among a representative sample of Rhode Island women with disabilities who recently gave birth. Methods: Data from the 2002–2011 Rhode Island Pregnancy Risk Assessment Monitoring System survey were analyzed. Results: Approximately 7% of women in Rhode Island reported a disability. Women with disabilities reported significant disparities in their health care utilization, health behaviors, and health status before and during pregnancy and during the postpartum period. Compared with nondisabled women, they were significantly more likely to report stressful life events and medical complications during their most recent pregnancy, were less likely to receive prenatal care in the first trimester, and more likely to have preterm births (13.4%; 95% CI, 11.6–15.6 compared with 8.9%; 95% CI, 8.5–9.3 for women without disabilities) and low–birth-weight babies (10.3%; 95% CI, 9.4–11.2 compared with 6.8%; 95% CI, 6.8–6.9). There was no difference in the rates of cesarean section between women with and without disabilities. Conclusions: These findings support the need for clinicians providing care to pregnant women with disabilities to be aware of the increased risk for medical problems during pregnancy and factors that increase the risk for poor infant outcomes.